Exploring the Role of Self-Regulated Learning and Technology Acceptance in Shaping EFL Student Teachers’ TPACK during Teaching Practicum - Dewi, Nita Sari Narulita; Supriyono, Yusup (ELITE JOURNAL, 2026)
The growth of Technological Pedagogical Content Knowledge (TPACK) among EFL student teachers during their teaching practicum is examined in this study in relation to self-regulated learning (SRL) and technology acceptance (TA). Three student teachers' semi-structured interviews, reflective journals, and lesson plans were all examined using a qualitative case study design. According to thematic analysis (Braun & Clarke, 2006), it is revealed that their lesson preparation, decision-making, and reflective practices were influenced by SRL processes like planning, monitoring, and reflection. Simultaneously, TA beliefs, which emphasize usefulness and ease of use, increased self-assurance, motivation, and digital tool experimentation. The findings show that both SRL and TA contributed to the development of TPACK by providing the necessary metacognitive support and motivation, respectively. Therefore, to support technology-enhanced pedagogy, teacher education programs ought to promote reflective SRL practices and constructive TA beliefs